Flux enhancement with gas injection in crossflow ultrafiltration of oily wastewater - Um, MJ; Yoon, SH; Lee, CH; Chung, KY; Kim, JJ (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
The gas injection technique was introduced to achieve flux improvement in cross-flow ultrafiltration of oil emulsion. By the nitrogen gas injection, homogeneous liquid phase oil/water emulsion was changed to heterogeneous gas-liquid phase. The injected gas causes positive effect of promoting turbulence, but it also has negative effect of decreasing the effective membrane area due to the partial occupation of membrane pores by bubbles. The efficiency of the gas injection was found out to be dependent on bubble fractions in the mixture: at sufficient bubble fractions the higher flux was observed, but at lower bubble fractions the flux rather decreased compared with that without gas injection. An attempt was made to explain the mechanisms for the dual aspects of gas injection. Turbulence dampening effect was also observed when the dependence of mass transfer coefficient on cross-flow rate was investigated with gas injection. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: PROTEIN FRACTIONATION; TUBULAR MEMBRANE; DEAN VORTICES; FILTRATION; MICROFILTRATION; SUSPENSIONS; FILTER; SYSTEM